Jake Drake, bully buster - Clements, Andrew, 1949-; Harvey, Amanda (New York : Aladdin Paperbacks, 2001)
Provides the "memoirs" of Jake Drake, a boy who transformed himself from first-grade geek to the cool dude of the fourth grade by using his wit to outsmart the bullies at his school.
"Ready-for-chapters"--Cover.
460
Keywords: Bullies -- Fiction; Schools -- Fiction